Embedding and disembedding of political elites: a filter system approach - Davis, Aeron (Sociological Review, 2015)
This article looks at the issue of political disengagement in mature democracies and the growing tendency towards disconnect between citizens and their political representatives. It locates itself in relation to 'demand-side' (external to politics) and critical 'supply-side' (focused on the political centre) explanations of disengagement. It concentrates on the latter and, accordingly, builds on critical, post-Marxist and elite-oriented work. As such it follows on from earlier calls in the journal for a return to elite-based research ( Savage and Williams, 2008). Drawing on general concepts in economic sociology ( Polanyi, Granovetter) the article presents an alternative embedding-disembedding paradigm for explaining and evaluating this tendency towards political elite disengagement. The propensity for politicians to disembed from wider society is explained by way of a series of eight 'filters'. Such filters work, alone or cumulatively, both to socially embed political elites within the institutions and networks of formal politics and also to disembed them from wider society and the populace they represent. The interpretive framework outlined here draws on a combination of secondary literature and ongoing interview-based research with some 150 political actors (politicians, journalists, officials) working at Westminster. As such, the filters and embedding-disembedding paradigm focuses primarily on the UK case. However, the framework is easily adaptable to other nations and systems.
Sociology
Keywords: Great Britain - politics & government; communication; disengagement; elite (social sciences); embedding/disembedding; organizations; political communication; political elites; political organizations; political participation laws; politicians